Microbial adaptations at higher altitude for sustainable development: A review - Manali Singh, Kuldeep Jayant, Dipti Singh, Deep Chandra Suyal, Abhirup Mitra, Shivani Bhutani (Journal of Applied Pharmaceutical Science, 2023)
The phyllospheric microbiome and rhizosphere, as well as microbial diversity inhabiting harsh environmental conditions, are studied extensively in the hilly regions. Difficult topography, poor infrastructure, and fragile ecosystems characterize hill agroecosystems. Thus, determining the precise process that determines biodiversity becomes extremely challenging. Plant-microbial interactions may explain why plants evolve to survive. Plant-microbial interactions may be a factor for plants’ adaptation approach to survive. Thus, plant–microbe interactions are extremely valuable since they are responsible for practically all biological transformations and the generation of consistent and balanced sources of nitrogen, carbon, and other nutrients that aid in the subsequent growth of plant communities. As a result, it aids in nutrient acquisition and accumulation. These plant-microbial interactions also aid in bioremediation and land restoration. As a result, the first processes of soil formation and nutrient input are dependent on the activity of plant–microbe interactions. Those bacteria that can endure the extremely cold climate at higher altitudes are critical for plant development. To survive in harsh environmental circumstances, microorganisms evolved in a variety of environments. As a result, it is critical to discover the powerful microorganisms and the mechanisms that allow them to live under extreme temperature circumstances. Later, similar ideas can be applied by farmers in field experiments for long-term agricultural production in the world’s coldest and harshest regions. This paper includes a brief examination of potential plant–microbe interactions as well as adaptive methods employed by plants and microbial biodiversity living in hilly locations.
Keywords: Microbes, adaptation, psychrophiles, extreme environment, PGPR